2020
DOI: 10.11144/javeriana.upsy19.mscm
|View full text |Cite
|
Sign up to set email alerts
|

Mejora de la satisfacción corporal en la madurez a través de un programa específico de imagen corporal

Abstract: Se compara la mejora lograda en satisfacción corporal por un programa específico de intervención en imagen corporal en personas mayores con los resultados obtenidos en programas de intervención y animación social, con el propósito de valorar si son significativamente mejores que otros programas de carácter social.  De ser así, resulta relevante intervenir específicamente sobre la satisfacción corporal durante la vejez para evitar otros problemas relacionados como la depresión o la baja autoestima. En el estudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…This notion is echoed by one participant's metaphorical depiction, describing how they planted a "seed" that gradually flourished over the months. This effect has already been seen in other therapeutic areas, as shown by recent studies such as Barrett and Stewart [75], who observed it in similar mindfulness-based techniques, or Sánchez-Cabrero [74] in the prevention of disorders related to body image.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This notion is echoed by one participant's metaphorical depiction, describing how they planted a "seed" that gradually flourished over the months. This effect has already been seen in other therapeutic areas, as shown by recent studies such as Barrett and Stewart [75], who observed it in similar mindfulness-based techniques, or Sánchez-Cabrero [74] in the prevention of disorders related to body image.…”
Section: Discussionmentioning
confidence: 52%
“…This is an ordinal within-subject variable with three levels: pre-treatment, posttreatment, and follow-up (11 months after the completion of the pilot study). Including this variable aims to assess the stability of the effect of the designed program once the initial momentum of the treated topics fades from participants' recent memory, thus avoiding confusion between the effects caused by the intervention and those caused by experimental maturation, as reported in numerous similar previous studies [73,74].…”
Section: Within-subject Intervening Variable: Evolution Over Timementioning
confidence: 99%
“…The bottom line is that, although lite products provide fewer calories, some do so by replacing fat with sugars and sweeteners that give them greater palatability. Another important aspect is the tendency to consume more of the product thinking that it can be abused because it is lite, which leads to the fact that, in many cases, the consumption of these products is directly associated with weight gain, not with the weight reduction they claim (Sánchez-Cabrero et al 2019;Sánchez-Cabrero 2020;Zandstra et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is a fact that eating habits in Western societies are closely affected by beauty standards (Mckay et al 2018;Sánchez-Cabrero et al 2020). In Spain, the interest in eating habits has grown faster, either by the influence of beauty standards or by the obsession with being young and healthy (De Los Santos-Mantero 2018;Sánchez-Cabrero et al 2019;Sánchez-Cabrero 2020;Díaz-Méndez 2006).…”
Section: Introductionmentioning
confidence: 99%
“…El cambio de la percepción del nivel medio superior al de licenciatura, donde la satisfacción aumenta significativamente, se asocia al proceso de construcción de identidad personal y social, que, a su vez, se relaciona con los cambios físicos producidos por la edad (Cadena-Duarte y Cardozo, 2021). También, la menor satisfacción con la apariencia física entre los más jóvenes respecto a los estudiantes de licenciatura tiene que ver con la distorsión perceptiva asociada a las dimensiones y apariencia de su cuerpo físico que desaparece con la madurez en forma progresiva (Sánchez, 2020).…”
Section: Apariencia Físicaunclassified